Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2010)
Networks has always been a place for sharing interesting and cutting edge work. This issue of Networks is no exception. Each of the articles presented in this issue presents a unique and intriguing look at the worlds of teaching, the questions educators are asking, and the ways teachers are making sense of their worlds. In this issue, both the voices of teachers and teacher educators tell powerful tales about their work and the lessons they have learned through teacher research.